Fresh versus frozen embryo transfers in assisted reproduction - Zaat, Tjitske (Cochrane Database Syst Rev, 2021)
BACKGROUND: In vitro fertilisation (IVF) or intracytoplasmic sperm injection (ICSI) treatments conventionally consist of a fresh embryo transfer, possibly followed by one or more cryopreserved embryo transfers in subsequent cycles. An alternative option is to freeze all suitable embryos and transfer cryopreserved embryos in subsequent cycles only, which is known as the 'freeze all' strategy. This is the first update of the Cochrane Review on this comparison. OBJECTIVES: To evaluate the effectiveness and safety of the freeze all strategy compared to the conventional IVF/ICSI strategy in women undergoing assisted reproductive technology. SEARCH METHODS: We searched the Cochrane Gynaecology and Fertility Group Trials Register, CENTRAL, MEDLINE, Embase, PsycINFO, CINAHL, and two registers of ongoing trials from inception until 23 September 2020 for relevant studies, checked references of publications found, and contacted study authors to obtain additional data. SELECTION CRITERIA: Two review authors (TZ and MZ) independently selected studies for inclusion, assessed risk of bias, and extracted study data. We included randomised controlled trials comparing a 'freeze all' strategy with a conventional IVF/ICSI strategy including a fresh embryo transfer in women undergoing IVF or ICSI treatment. DATA COLLECTION AND ANALYSIS: The primary outcomes were cumulative live birth rate and ovarian hyperstimulation syndrome (OHSS). Secondary outcomes included effectiveness outcomes (including ongoing pregnancy rate and clinical pregnancy rate), time to pregnancy and obstetric, perinatal and neonatal outcomes. MAIN RESULTS: We included 15 studies in the systematic review and eight studies with a total of 4712 women in the meta‐analysis. The overall evidence was of moderate to low quality. We graded all the outcomes and downgraded due to serious risk of bias, serious imprecision and serious unexplained heterogeneity. Risk of bias was associated with unclear blinding of investigators for preliminary outcomes of the study during the interim analysis, unit of analysis error, and absence of adequate study termination rules. There was an absence of high‐quality evidence according to GRADE assessments for our primary outcomes, which is reflected in the cautious language below. There is probably little or no difference in cumulative live birth rate between the 'freeze all' strategy and the conventional IVF/ICSI strategy (odds ratio (OR) 1.08, 95% CI 0.95 to 1.22; I(2) = 0%; 8 RCTs, 4712 women; moderate‐quality evidence). This suggests that for a cumulative live birth rate of 58% following the conventional strategy, the cumulative live birth rate following the 'freeze all' strategy would be between 57% and 63%. Women might develop less OHSS after the 'freeze all' strategy compared to the conventional IVF/ICSI strategy (OR 0.26, 95% CI 0.17 to 0.39; I(2) = 0%; 6 RCTs, 4478 women; low‐quality evidence). These data suggest that for an OHSS rate of 3% following the conventional strategy, the rate following the 'freeze all' strategy would be 1%. There is probably little or no difference between the two strategies in the cumulative ongoing pregnancy rate (OR 0.95, 95% CI 0.75 to 1.19; I(2) = 31%; 4 RCTs, 1245 women; moderate‐quality evidence).  We could not analyse time to pregnancy; by design, time to pregnancy is shorter in the conventional strategy than in the 'freeze all' strategy when the cumulative live birth rate is comparable, as embryo transfer is delayed in a 'freeze all' strategy. We are uncertain whether the two strategies differ in cumulative miscarriage rate because the evidence is very low quality (Peto OR 1.06, 95% CI 0.72 to 1.55; I(2) = 55%; 2 RCTs, 986 women; very low‐quality evidence) and cumulative multiple‐pregnancy rate (Peto OR 0.88, 95% CI 0.61 to 1.25; I(2) = 63%; 2 RCTs, 986 women; very low‐quality evidence). The risk of hypertensive disorders of pregnancy (Peto OR 2.15, 95% CI 1.42 to 3.25; I(2) = 29%; 3 RCTs, 3940 women; low‐quality evidence), having a large‐for‐gestational‐age baby (Peto OR 1.96, 95% CI 1.51 to 2.55; I(2) = 0%; 3 RCTs, 3940 women; low‐quality evidence) and a higher birth weight of the children born (mean difference (MD) 127 g, 95% CI 77.1 to 177.8; I(2) = 0%; 5 RCTs, 1607 singletons; moderate‐quality evidence) may be increased following the 'freeze all' strategy. We are uncertain whether the two strategies differ in the risk of having a small‐for‐gestational‐age baby because the evidence is low quality (Peto OR 0.82, 95% CI 0.65 to 1.05; I(2) = 64%; 3 RCTs, 3940 women; low‐quality evidence). AUTHORS' CONCLUSIONS: We found moderate‐quality evidence showing that one strategy is probably not superior to the other in terms of cumulative live birth rate and ongoing pregnancy rate. The risk of OHSS may be decreased in the 'freeze all' strategy. Based on the results of the included studies, we could not analyse time to pregnancy. It is likely to be shorter using a conventional IVF/ICSI strategy with fresh embryo transfer in the case of similar cumulative live birth rate, as embryo transfer is delayed in a 'freeze all' strategy. The risk of maternal hypertensive disorders of pregnancy, of having a large‐for‐gestational‐age baby and a higher birth weight of the children born may be increased following the 'freeze all' strategy. We are uncertain if 'freeze all' strategy reduces the risk of miscarriage, multiple pregnancy rate or having a small‐for‐gestational‐age baby compared to conventional IVF/ICSI.